Preparation and characterisation of porous silicon and porous silicon based composite materials - Balakrishnan, Sivakumar (Trinity College (Dublin, Ireland). School of Chemistry, 2006)
The main aim of the thesis was to develop new advanced materials based on porous silicon. In chapters II and III, the fabrication of porous silicon by electrochemical etching using different aqueous and organic electrolytes have been explored. The structure and properties of porous silicon such as porosity, thickness and pore depth were studied as a function of etching parameters and anodisation conditions which include HF concentration, current density, silicon resistivity etc. We have demonstrated that using conductive salts (here TBAP) in HF-DMF solution allows the etching of silicon samples with higher current density. A similar process without conductive salts would result in electropolishing.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin